Investigating the Intracellular Trafficking of Polymeric Vectors for Gene Delivery - Shi, Julie (My University, 2013)
Gene therapy has the potential to revolutionize the treatment of diseases caused by genetic mutations. The development of effective, biocompatible synthetic gene delivery vectors can be improved by understanding the intracellular trafficking processes of these vectors. Part I focuses on the mechanistic evaluation of parameters that may be important for nonviral gene delivery. Chapter 1 provides a short introduction to nonviral gene delivery, methods used to determine the intracellular distribution of nonviral vectors, and general development of fractionation methods for determining the intracellular distribution of biologics. Chapter 2 uses the methods optimized in Chapter 1 to determine the bulk intracellular distribution of a synthetic cationic polymer carrier and cargo DNA in a cultured cell line. Chapter 3 is a mechanistic evaluation of the role of particle morphology on gene transfer. In Part II, we describe the development of peptide-functionalized materials for gene delivery. Chapter 4 is a review of the synthetic peptide-polymers developed in the Pun lab. Chapter 5 describes the incorporation of degradable segments into the peptide-polymers, while Chapter 6 describes the incorporation of an endosomal buffering peptide into these polymers. Finally, a new approach to identifying intracellular targeting ligands to a model organelle is described in Chapter 7. Chapter 8 concludes with recommendations for future work based on our findings.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: cellular fractionation; gene delivery; nonviral vectors; particle morphology; peptides; Biomedical engineering; bioengineering